Colchicine as an Anti-Inflammatory Agent in Atherosclerosis-Mediated Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA): A Systematic Review - Patel, Pushpraj; Mishra, Anjeney; Patel, Akhilesh; Patel, Kaveri Shaw; Ashok, Darnule Rahul; Gawande, Sachin (British Journal of Healthcare and Medical Research, 2026)
Background: Myocardial infarction with non-obstructive coronary arteries (MINOCA) represents 5–15% of all acute myocardial infarctions (AMI) and disproportionately affects younger patients and women. Atherosclerosis-driven inflammation via the NLRP3 inflammasome pathway is increasingly recognized as a pivotal mechanism. Colchicine, an ancient alkaloid with potent anti-inflammatory properties, has emerged as a promising therapeutic agent in this setting. Objective: To systematically evaluate the evidence for colchicine as an anti-inflammatory agent in atherosclerosis-mediated MINOCA, including its mechanisms of action, clinical efficacy, and safety profile. Methods: A comprehensive search of PubMed/MEDLINE, Embase, Cochrane Library, and ClinicalTrials.gov was conducted from inception through December 2023. Studies examining colchicine in MINOCA, acute coronary syndromes, and atherosclerotic cardiovascular disease were included. PRISMA guidelines were followed throughout. Results: Thirteen studies (5 RCTs, 4 prospective cohort studies, 4 retrospective studies) comprising 15,428 patients met inclusion criteria. Colchicine significantly reduced major adverse cardiovascular events (MACE) by 23–31%, with reduction in high-sensitivity C-reactive protein (hs-CRP) by 38–56%. In MINOCA-specific analyses, colchicine attenuated the NLRP3 inflammasome cascade, reduced IL-1β and IL-18 levels, and suppressed neutrophil-mediated endothelial injury. Adverse effects were predominantly gastrointestinal, occurring in 7.1–10.5% of patients. Conclusion: Colchicine demonstrates consistent anti-inflammatory efficacy in atherosclerosis-mediated MINOCA. Its favorable safety profile at low doses (0.5 mg/day) and compelling mechanistic rationale support its incorporation into MINOCA management guidelines. Dedicated randomized trials in MINOCA populations are warranted.